The Influence Of Local Taxes And Local Levies On The Regional Original Income Of Jakarta Special Capital Region DKI Jakarta - Asyah Harisandi, Ashila; Akhfanabila, Nadya; Windiana Kirani, Rizky; Saleh Sadikin, Dikdik; Idawati, Wiwi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
The covid-19 pandemic has caused a decline in growth in several sectors of the Indonesian economy. However, this does not affect DKI Jakarta's local revenue because based on data obtained by the Central Bureau of Statistics, it continues to increase every year even though the economy has slumped during the pandemic. This study aims to determine and analyse the effect of local taxes and levies on local revenue in DKI Jakarta Province for the period 2010-2022. The data used in this study are secondary data obtained through quantitative methods. The population and samples used are the realisation reports of the Regional Revenue and Expenditure Budget for the period 2010-2022. The analysis method used in this research is multiple linear regression analysis, including normality test, classical assumptions, and hypothesis testing. Partial research results show that local taxes have a positive effect on regional original income, while local levies has no significant effect on regional original income. Simultaneously, local tax and local levies have a positive influence on regional original income. A well-managed local tax will increase local revenue, which will logically increase regional original income. Meanwhile, regions that experience difficulties in managing and collecting retribution, including the lack of supporting infrastructure and inadequate human resources, cause the low contribution of retribution to regional original income.